Forensic Analysis of some Tooth Pastes of Indian Brand (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
In the present work, studies have been carried out on the formulation and evaluation of various toothpaste brands available in Indian market. The designed toothpaste samples were analysed for various parameters and characteristics, which were conceded out for all the available samples. Physical parameters such as efficacy, performance, quality and sensitivity were tested according to the Bureau of Indian Standards, while chromatographic analysis of chlorates of alkali metals and chloroform were based on the European Directive. Our findings indicated that all the toothpaste formulations complied with the standards specified with Bureau of Indian Standards and are in agreement with manufacturer’s specifications. All the products in lieu with forensic toxicology were found to be safe, compatible with packaging, compliant with current legislative constraints and capable of performing as they claimed.
Keywords: Toothpaste; Cosmetic; Cosmeceuticals; Bureau of Indian standards; Forensic Toxicology; Thin layer chromatography; Gas chromatography